High HIV Positivity Rates Following Large-Scale HIV Self-Testing Implementation in Zimbabwe, 2018–2020 - Muchedzi, Auxilia; Mpofu, Mulamuli; Mudzengerere, Fungai H.; Bateganya, Moses; Mavimba, Tarirai; Satti, Hind; Dhliwayo, Rumbidzai; Zulu, Tinashe; Tapera, Talent; Samushonga, Tendai; Nyagura, Tendai; Ncube, Getrude; et al. (Frontiers in Public Health, 2021)
Introduction: HIV self-testing (HIV-ST) is an innovative strategy to increase HIV case identification and can be implemented while maintaining physical distancing. This analysis shares the outcomes of HIV-ST implementation within the Zimbabwe HIV Care and Treatment (ZHCT) project and demonstrate the relevance of the results in bridging the HIV testing gap during the COVID-19 period and beyond. Materials and methods: We extracted HIV-ST data for the period October 2018 to March 2020 from the project database and assessed 1)the proportion of reactive HIV-ST results; 2) the concordance between reactive HIV-ST results against rapid confirmatory HIV tests using Determine™ and Chembio™ in parallel; and 3) the monthly contribution of HIV-ST to total HIV positive cases identified within project. The Chi-square test was used to assess for differences in proportion of cases identified through HIV-ST and through index and mobile testing by age group, gender, and month. Findings: Between October 2018 and March 2020, the ZHCT project distributed 11,983 HIV-ST kits, where 11,924 (99·8%) were used and 2,616 (21.9%) were reactive. Of the reactive tests, 2,610 were confirmed HIV positive, a concordance rate of 99·8% between the HIV-ST results and the confirmatory tests. Proportion of reactive results differed by age-groups; with the 30-34, 35-39- and 40-44-year age groups having the highest proportions above 25% (p<.001). HIV-ST contributed less than 10% of new positives at roll-out and this significantly increased to 80% at the end of March 2020 (p<.001). Conclusion: The ZHCT project has successfully scaled up HIV self-testing which is contributing significantly to HIV case finding. Given the current COVID-19 challenges these results demonstrate the potential of HIV-ST in closing the HIV testing gap because it can be implemented while maintaining physical distancing